2007
DOI: 10.1103/physreva.76.052517
|View full text |Cite
|
Sign up to set email alerts
|

Müller’s exchange-correlation energy in density-matrix-functional theory

Abstract: The increasing interest in the Müller density-matrix-functional theory has led us to a systematic mathematical investigation of its properties. This functional is similar to the Hartree-Fock ͑HF͒ functional, but with a modified exchange term in which the square of the density matrix ␥͑x , xЈ͒ is replaced by the square of ␥ 1/2 ͑x , xЈ͒. After an extensive introductory discussion of density-matrix-functional theory we show, among other things, that this functional is convex ͑unlike the HF functional͒ and that e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
0
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(100 citation statements)
references
References 39 publications
1
95
0
4
Order By: Relevance
“…Müller's functional satisfies both conditions 20 for all p with 0 Ͻ p Ͻ 1. All studies of this functional to date have set p =1/ 2 ͑in the rest of the paper we refer to this as the Müller functional͒.…”
Section: ͑1͒mentioning
confidence: 99%
“…Müller's functional satisfies both conditions 20 for all p with 0 Ͻ p Ͻ 1. All studies of this functional to date have set p =1/ 2 ͑in the rest of the paper we refer to this as the Müller functional͒.…”
Section: ͑1͒mentioning
confidence: 99%
“…4,15,28 It was recently shown by Frank et al 36 that for two electron systems the Müller functional provides a lower-bound for the total energy. They also showed that, for this functional, the total energy does not go to zero if the ionic potential is switched off but to the value −N/8 a.u.…”
Section: Functionalsmentioning
confidence: 99%
“…In particular, we perform self-consistent Hartree-Fock (HF) calculations and, in addition, study a similar self-consistent variational procedure using the so-called Müller density matrix functional (replacing the Fock term). 30,31 In atomic physics applications, the Müller functional is sometimes superior to the HF approach and is valuable because it yields a lower bound for the ground-state energy. 31 We note that HF calculations for graphene dots with infinite-mass confine-ment have also been carried out by other groups.…”
Section: Introductionmentioning
confidence: 99%